2017
DOI: 10.3390/e19090460
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Parameter Selection in Fixed Sample Entropy of Surface Diaphragm Electromyography for Estimating Respiratory Activity

Abstract: Fixed sample entropy (fSampEn) is a robust technique that allows the evaluation of inspiratory effort in diaphragm electromyography (EMGdi) signals, and has potential utility in sleep studies. To appropriately estimate respiratory effort, fSampEn requires the adjustment of several parameters. The aims of the present study were to evaluate the influence of the embedding dimension m, the tolerance value r, the size of the moving window, and the sampling frequency, and to establish recommendations for estimating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Sampling frequency is another parameter to be taken into account in fSampEn calculation. It has been reported that higher sampling frequencies yield lower fSampEn values [26]. However, the effect of sampling frequency in fSampEn time-series can be omitted if sampling frequency is correctly chosen based on the effective bandwidth of each type of myographic respiratory signal, as in the present study.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Sampling frequency is another parameter to be taken into account in fSampEn calculation. It has been reported that higher sampling frequencies yield lower fSampEn values [26]. However, the effect of sampling frequency in fSampEn time-series can be omitted if sampling frequency is correctly chosen based on the effective bandwidth of each type of myographic respiratory signal, as in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…The m parameter is typically set at 1 or 2 [16,37]. In recent studies by our group, no relevant differences were found between m = 1 and m = 2 for fSampEn calculation in sEMG lic signals [26], and m = 2 has been properly used for the analysis of different myographic respiratory signals [6]. Accordingly, m = 2 has also been used in the present study for the analysis of myographic respiratory signals.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations